LEGAL CONSEQUENCES OF LOSS OF FIDUCIARY GUARANTEE OBJECT IN BANK CREDIT AGREEMENT - Sadewo, Imron; Rokhim, Abdul (International Significance of Notary, 2022)
The banking industry is one of the important components in the national economy which aims to maintain a balance in the progress and unity of the national economy itself, the stability of the banking industry itself is very influential in overall economic stability as experienced from the occurrence of the monetary and banking crisis in Indonesia in 1998, With the existence of a guarantee agreement that was agreed at the beginning when the agreement was being held that the debitor must provide a fiduciary guarantee like  movable property such as a car, with this way the collateral object must exist so that with the collateral object (car), then this has been limited to other collateral objects such as immovable collateral objects such as certificates of houses, land and so on. The formulation of the problems to be discussed are (1) What are the legal consequences of the bank's credit agreement for the loss of the fiduciary guarantee object due to the negligence of the debtor? (2) What are the legal remedies taken by creditors for the loss of fiduciary collateral objects due to the debtor's negligence? The research method of this thesis uses normative research method, it means that the issues raised, discussed and described in this research are focused on applying the rules or norms in positive law. The problem approach uses a statutory approach and a conceptual approach with legal materials consisting of primary, secondary and tertiary legal materials. The research results show that: First, the legal consequences of the agreement for the loss of the fiduciary guarantee object due to the debtor's negligence is the credit agreement does not have a fiduciary guarantee, so that the debtor's position changes from a preferred creditor (prefent) with special material guarantees (fiduciary) to a concurrent creditor who does not have special material guarantees. Second, the legal remedies taken are (a) asking the debtor to immediately return the credit loan to the creditor as a responsibility for the collateral that has been lost; and/or (b) suing for compensation for lost fiduciary collateral objects based on article 1365 of the Civil Code Keywords: loss of objects of fiduciary guarantees, bank credit agreements